(3GdEJUGd GdOHdheGSj aj Xd KhQI GdEJUGds - (3fUjQI (B, (3NGdaj s ((3YeGf (B:s (3OGQ GdMGeO(B,s, 2019)
(3GdGJUGd GdOHdheGSj eYfGg h CHYGOg , cPdc GdKhQI GdGJUGdjI eaghegG h GdJWhQGJ h GdJCKjQGJ ceG JMOK Yf JCKjQ GdKhQI GdGJUGdjI Ydi COhGJ h CgOGa GdGJUGd GdOHdheGSj h Ydi GdGWGQ GdeDSSj ddGJUGd GdOHdheGSj (B.s
(3eQGLY U(B.379s
Keywords: (3GdGJUGd GdSjGSjs; (3GdGfJQfJs; (3GdOHdheGSjIs